ASSESSMENT OF CARDIOVASCULAR AND RENAL OUTCOMES FOLLOWING DAPAGLIFLOZIN THERAPY IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AND CHRONIC KIDNEY DISEASE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a major cause of chronic kidney disease (CKD) and cardiovascular morbidity worldwide. Despite adequate glycemic control, many patients continue to experience progressive renal dysfunction and adverse cardiovascular outcomes. Dapagliflozin, a sodium-glucose cotransporter-2 (SGLT2) inhibitor, has demonstrated significant cardiorenal protective effects beyond glucose lowering. Aim: To evaluate the cardiovascular and renal outcomes of dapagliflozin in patients with Type 2 diabetes mellitus and chronic kidney disease. Methodology: This prospective observational comparative study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from November 2024 to December 2025. A total of 60 patients with T2DM and CKD were enrolled and divided into two groups. Group A received dapagliflozin 10 mg once daily along with standard therapy, while Group B received standard therapy alone. Renal and cardiovascular parameters including glycated hemoglobin (HbA1c), fasting blood sugar (FBS), body weight, estimated glomerular filtration rate (eGFR), urinary albumin-to-creatinine ratio (UACR), and blood pressure were assessed at baseline, 3 months, 6 months, and 12 months. Statistical analysis was performed using SPSS version 25.0, and a p-value